Sociolinguistic and Geolinguistic Variation in the Basque language - Aurrekoetxea, Gotzon (Slavia Centralis, 2020)
In this contribution, we show the first results of the "Socio-geolinguistic atlas of the Basque language-EAS". This research project was presented at the Vth Congress of Dialectology and Geolinguistics held in Braga. On the one hand, we present some data collected in the same locality from informants of different generations (the elderly, adults and young people). We examine the linguistic differences that we found among people of these generations and we analyse whether the difference among generations is similar in all localities or not, or whether some of them have peculiar characteristics. On the other hand, we show different types of geolinguistic variation: variation among elderly people, adults or among young people.
Keywords: sociolinguistic variation; geolinguistic variation; corpus linguistics; Basque dialectology